The association between the level of adherence to the Mediterranean diet and successful aging: An analysis of the ATTICA and MEDIS (MEDiterranean Islands Study) epidemiological studies. (July 2020) - Foscolou, Alexandra; D'Cunha, Nathan M.; Naumovski, Nenad; Tyrovolas, Stefanos; Chrysohoou, Christina; Rallidis, Loukianos; Polychronopoulos, Evangelos; Matalas, Antonia-Leda; Sidossis, Labros S.; Panagiotakos, Demosthenes
Abstract: Aim: The aim of the present work was to evaluate the association between the level of adherence to the Mediterranean diet and successful aging, taking into consideration the overall dietary pattern, rather than individual foods, among middle-aged and older individuals. Methods: A harmonized dataset of middle-aged and older participants (>50 years old) from the ATTICA (n = 1, 128) and MEDIS (n = 2, 221) population-based cross-sectional studies was used. Socio-demographic, anthropometric, clinical and lifestyle characteristics were measured in both studies and harmonized using standardized procedures. Level of adherence to the Mediterranean diet was evaluated using the MedDietScore (range 0–55, "Low" adherence <34, "High">38). Successful aging was evaluated using the validated successful aging index (SAI, range 0−10) comprising of health-related, social, lifestyle and clinical characteristics. Results: Adherence to the Mediterranean diet was positively associated with SAI (b ± SE "High" vs. "Low": 1.094 ± 0.130, p < 0.001 and "Moderate" vs "Low": 0.476 ± 0.156, p = 0.003) . Conclusion: Higher adherence to the Mediterranean diet was independently associated with a higher level of successful aging. Mediterranean diet or dietary patterns that are close to this pattern, should be actively promoted and encouraged to middle aged and older people to achieve successful aging.